Analisis Dampak Pemanfaatan Gadget Pada Pembelajaran Pendidikan Agama Hindu dan Budi Pekerti Dalam Pembentukan Karakter Religius Peserta Didik Kelas VIII Di SMP Negeri 3 Mengwi - Made Yuristia Hany Bagia (UHN IGB Sugriwa Denpasar, 2025)
ABSTRACT In the 21st century, digitalization in various aspects of life including education. In Hindu Education and Ethics Learning, on the one hand, this gadget can help but have an impact on grade VIII students. The formulation of the problem: (1) The form of using gadgets in the learning of Hindu Religious Education and Ethics in the formation of religious character of grade VIII students at SMP Negeri 3 Mengwi? (2). What is the impact of using gadgets on the learning of Hindu Religious Education and Ethics in the formation of religious character of grade VIII students at SMP Negeri 3 Mengwi? (3). What efforts have Hindu teachers made to overcome the impact of using gadgets on the learning of Hindu Religious Education and Ethics in the formation of religious character of grade VIII students at SMP Negeri 3 Mengwi?The purpose of this research is to find out the form of gadget utilization, to analyze the impact of gadget use, to find the efforts of Hindu teachers in overcoming the impact of gadget use. The theories used are: Uses and Gratification Theory, Dependency Theory and Character Theory. The data collection method uses observation, interviews, literature studies, document studies with qualitative descriptive analysis. The results of the study showed that teachers used laptops and mobile phones with WhatsApps, Google, Youtube, Powerpoint, Quizizz and Google Form applications. This gadget has a positive and negative impact on students. Efforts that Hindu teachers can make in overcoming this problem are by supervising, reprimanding, providing ice breaking, providing direction, cooperating with parents and shaping the religious character of students. . Keywords: Gadgets, Hindu Religious Education Learning, Religious Character